Vremya reshayushchikh peremen - Kuzin, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to attract the public attention to the problems of the contemporary professional physical culture education. The author considers the next ways of improvements in the system of higher physical culture education to arise the quality of specialists' training and their further training.